Human trafficking in migratory processes: a manifestation of violence against women in America Latina - García Zamora, Ericka (2021)
This article exposes the current problem of trafficking vulnerable women and girls, aggravated by their gender and migration, in the geopolitical context of America Latina and South America. In order to accomplish this, it is analyzed the relation between trafficking in persons for the purpose of sexual and labor exploitation, and gender perspective. Plus, the way off recruitment according to the purpose of the capture of women to traffic whit them in America Latina’s context. The investigation clearly shows the link between gender and vulnerability; the evidence, as well shows the existing bond among that vulnerability and human trafficking.